The blindness of John Milton and Jacques Derrida - Sá, Luiz Fernando Ferreira; Mansur, Miriam Piedade (Laboratório Editorial FCL-UNESP, 2009)
The purpose of this essay on the visual metaphors of Paradise Lost is to demonstrate that John Milton’s phrase “darkness visible” and other lines of Paradise Lost, to a certain extent, adumbrated the post-structuralist stance on vision, that is, the need to mistrust the immediacy of physical sight and to search for a deeper reflection upon the superficiality of images. Milton’s “darkness visible” perspective is compatible, in the view of this essay, with that of Jacques Derrida in his book Memoirs of the Blind (1993). The Algerian-French philosopher proposes two types of blindness: the sacrificial and the transcendental. Through the oxymoron “darkness visible” and the sacrificial and transcendental types of blindness, John Milton and Jacques Derrida can be read alongside each other and point to the reading of “a paradise within” as ultimately associated with “a downward path to wisdom” and to “downcast eyes”.